Risk Factor Analysis of Occupational Diseases in Computer Users - IRWAN, Irwan; RIDHA, Nadirah Rasyid; KATILI, Deliyana I; UNA, Mar’atuljannah (International Journal of Environmental, Sustainability, and Social Science, 2023)
Eye fatigue disorders often occur in workers who use computers to carry out their daily activities. This study aims to determine the relationship between long exposure and monitor distance with eye fatigue disorders in computer users. This type of research is quantitative with an analytical survey method that uses a cross-sectional design. The population is computer operator workers, totaling 36 employees. The sampling technique was purposive sampling. They collect data using a questionnaire—analysis of the relationship between the independent and dependent variables using the chi-square test. This study proves that long exposure (5-6 hours without rest) and working at a distance from a computer monitor (<50 cm) poses a danger of eye fatigue. The study results showed that 96.7% of respondents who worked at a distance of <50 cm from the monitor experienced eye fatigue. The chi-square test analysis showed a relationship between the length of exposure and eye fatigue (? = 0.008) and a relationship between monitor distance and eye fatigue (? = 0.001). It is suggested that employees arrange the working time and monitor distance ergonomically.